2019
DOI: 10.21203/rs.2.17822/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The state of child nutrition in Ethiopia: an umbrella review of systematic review and meta-analysis reports

Abstract: Background Various systematic review and meta-analysis (SRM) studies were done on nutritional statuses of children in Ethiopia, but no summary of the findings was done on the topic. Thus, this umbrella review was done to summarize the evidence from SRM studies on the magnitude and determinants of malnutrition and poor feeding practices among under-5 children in Ethiopia.Methods PubMed, Embase, Scopus, Web of Sciences, and Google Scholar were searched for SRM studies on the magnitude and risk factors of malnutr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…In this study, child's age showed an independent negative association with hemoglobin status. This is consistent to the findings of studies conducted in other low-income countries (Huang et al, 2018;Mohammed, Habtewold, & Esmaillzadeh, 2019). Prolonged exclusive breastfeeding, delayed initiation of complementary foods, and initiating complementary feeding with poorly diversified diet could contribute for the lower hemoglobin levels in infants.…”
Section: Ta B L E 3 (Continued)supporting
confidence: 90%
“…In this study, child's age showed an independent negative association with hemoglobin status. This is consistent to the findings of studies conducted in other low-income countries (Huang et al, 2018;Mohammed, Habtewold, & Esmaillzadeh, 2019). Prolonged exclusive breastfeeding, delayed initiation of complementary foods, and initiating complementary feeding with poorly diversified diet could contribute for the lower hemoglobin levels in infants.…”
Section: Ta B L E 3 (Continued)supporting
confidence: 90%
“…The first overview study, which examined the trends and methodological quality of 35 SR and 17 MA published until 2018, showed that three-fourths of the studies had poor methodological quality. 9 The second and third overview studies were conducted on SR and MA of child nutrition (nine articles included) 10 and birth asphyxia (four articles included) 11 found moderate methodological quality. Recently, the fourth overview study was conducted by our group using 422 SR and MA that were published before December 31, 2021, and provided a detailed bibliometric information on the publication landscape of SR and MA in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…10.17605/osf.io/vapzx). All the supplementary methods and data are available in the publically open database in OSF (https://osf.io/q5dw2).…”
mentioning
confidence: 99%